Company Level Variables in R&D Cooperation Perspective - Alghamdi, Mohamad (Communications in Mathematics and Applications, 2020)
This paper aims to study the importance of cooperation in Research and Development (R&D) in the company level variables. The competition intensity and knowledge flow have impacts on those variables. However, these obstacles resulting from market structure and investment relationship may be reduced by expanding R&D relations.